Conditions of the development of electronic commerce in Poland - Pieczarka, Katarzyna (Uwarunkowania rozwoju handlu elektronicznego w Polsce, 2019)
The main aim of this article is to identify the contemporary determinants of the development of electronic commerce in Poland and state their influence on online businesses. In order to achieve this, descriptive statistics and statistical analysis, including comparative analysis, have been applied. On the basis of the examination, the contemporary growth factors (opportunities) in e-commerce such as m-commerce, Omnichannel commerce, Virtual Reality, and Augmented Reality can be characterised. The analysis also focuses on potential Internetrelated threats and their impact on e-businesses
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 92-102
Keywords: e-commerce; ICT; omnichannel commerce; mobile commerce; virtual reality; augmented reality; handel elektroniczny; handel wielokanałowy; handel mobilny; rzeczywistość wirtualna; rzeczywistość rozszerzona